A numerical study of spent nuclear fuel dry storage systems under extreme impact loading. (15th April 2018) - Hanifehzadeh, Mohammad; Gencturk, Bora; Mousavi, Reza
Highlights: Crash analysis of dry cask storage systems for spent nuclear fuel. Reinforced concrete (RC) and steel-concrete-steel sandwich casks evaluated. Mid-height impact shown to be most damaging. RC casks shows higher penetration and damage. 60 m/s velocity of a typical aircraft engine is lower bound for tip over. Abstract: The structural integrity of concrete dry storage systems under an impact loading caused by a simulated commercial airplane engine crash is evaluated in this study. A finite element model of a generic vertical dry storage system including the concrete overpack, multi-purpose canister, spent nuclear fuel (SNF) basket, and SNF assemblies was developed using a commercial finite element analysis software. The strain rate effect was considered for the steel parts of the cask via a rate dependent and nonlinear constitutive model. The modeling approach was first validated using experimental data available in literature on projectile impact of concrete and steel/concrete composite (sandwich) panels. Then, a comprehensive comparison in terms of strains, damage and deformations was performed for two configurations of reinforced and sandwich cask overpacks commonly used in the industry. Critical impact height was identified by an examination of the strains and accelerations in the SNF assemblies. Furthermore, the effect of boundary conditions for the two cases of free-standing and anchored configuration was investigated. The maximum deformation and stress as well as the peak acceleration were identified in the SNF basket to assess safety of the SNF assemblies. The minimum impact velocity causing tip-over from aircraft engine impact was determined.